How WEIRD are the South African acute pain guidelines? An analysis of the 2015 South African acute pain guidelines - Deedat, Raees (Department of Anaesthesia and Perioperative Medicine, 2023)
Background: There is increasing recognition that health care research is biased owing to skewed reliance on data from WEIRD (Western, Educated, Industrialized, Rich, Democracies) populations. This research explores health care discrepancy, primarily experienced by non-westernised, non-industrialised, non-rich and non-white people in the context of formulating the South African Acute Pain Guidelines, 2015 as published by the South African Society of Anaesthesiologists (the extant protocol at the time of writing). Methods: An established, peer-reviewed and published WEIRD (Western, Educated, Industrialized, Rich, Democracies) / non-WEIRD protocol for categorizing clinical population datasets was applied to the published datasets used in formulating the 2015 South African Acute Pain Guidelines. Results: A total of 5,246,847 patient data points were included in the numerous studies that formed part of the final analysis. Only 1% (n=73,539) of the patient data points originated from countries classified as nonWEIRD. Conclusions: The results confirmed the hypothesis that the 2015 South African Acute Pain Guidelines are based primarily on data from WEIRD population datasets. This study reveals an important type of bias in the scientific pain literature and also demonstrates a form of analysis that will encourage future published guidelines and research to be more inclusive of the depth and diversity of South African clinical practice.